Prevalence and Associated Factors of Anemia Among Pregnant Women Attending Antenatal Care at Mizan Aman General Hospital, Bench Maji Zone, Southwest, Ethiopia - Kaleab Tesfaye Tegegne; Seblework Abeje; Eleni Tesfaye Tegegne; Mekibib Kassa Tessema; Tadele Kassahun Wudu (Anemia)
Conclusion: Anemia in pregnant women is found to be a moderate public health issue in the research location. It is strongly and independently impacted by malaria infection and iron-containing meal consumption. Reducing the prevalence of anemia is made possible by improved iron-containing meal consumption. In addition, it is strongly advised that pregnant women receive education and should take iron supplements during pregnancy visits.